2018
DOI: 10.21608/jacb.2018.36313
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cyanobacteria for Controlling Flax Seedling Blight

Abstract: Cyanobacteria are one of important groups of prokaryotes due to their effects on growth and development of plants and its role in biological control of phytopathogenic fungi such as : Fusarium oxysporum and Rhizoctonia solani on flax by producing various biologically active substances . In the present study , fourteen cyanobacterial strains were isolated from rice rhizosphere in kafr Elsheikh (k) ( North Delta Region ) and El-Dakahliya (D) ( East Delta Region ) . Only five cyanobacterial strains showed antagon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Arthrospira platensis extract contains phenolics resulting in antifungal activity [ 22 ]. Anabaena , when applied to seeds, resulted in the protection of root diseases from fungal pathogens such as Fusarium [ 23 ] through different mechanisms such as phosphate solubilization and indole-3-acetic acid (IAA), ammonia, hydrogen cyanide (HCN), and enzyme production [ 24 ]. Today, the risk of fungal plant disease is one of the most urgent issues [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Arthrospira platensis extract contains phenolics resulting in antifungal activity [ 22 ]. Anabaena , when applied to seeds, resulted in the protection of root diseases from fungal pathogens such as Fusarium [ 23 ] through different mechanisms such as phosphate solubilization and indole-3-acetic acid (IAA), ammonia, hydrogen cyanide (HCN), and enzyme production [ 24 ]. Today, the risk of fungal plant disease is one of the most urgent issues [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous studies reported that the chitinase enzyme produced by Volvox carteri appeared to play a defensive role in protecting the plants from pathogenic fungi [78,79]. Moreover, cyanobacterial strains effectively protected flax from infection by soil-borne fungi due to chitinase and catalase enzymes [80]. Cyanobacteria can synthesize and release enzymes that directly attack the cell walls of pathogens.…”
Section: Discussionmentioning
confidence: 98%
“…Bacterial strains may protect plants from phytopathogens by production some materials such as ammonia, hydrogen cyanide and catalase (Kremer andSouissi 2001 &Khan et al 2018). All of the products improved plant growth by the production growth regulators substances like IAA (Hameeda et al 2008 &Ashour 2018). Among the four strains of Bacillus spp.…”
Section: Detection Of Antagonistic Substances By Bacterial Isolatesmentioning
confidence: 99%
“…Additionally, some bacteria produce hydrolytic cellulases synergistic action by endoglucanase, exoglucanase or cellobiohydrolase and ß-glucosidase (Lynd, 2002). In addition, the bioagents materials showed that all bacterial strains produced ammonia and catalase enzyme (Afify and Ashour 2024).…”
Section: Detection Of Antagonistic Substances By Bacterial Isolatesmentioning
confidence: 99%